Restoring livelihoods after the 2025 Myanmar earthquake: Pre-crisis baseline for recovery planning - Masias, Ian; van Asselt, Joanna; Minten, Bart (International Food Policy Research Institute, 2025)
On March 28, 2025, a 7.7 magnitude earthquake struck central Myanmar, causing extensive destruction and compounding an already fragile humanitarian situation driven by conflict, economic instability, and prior natural disasters. This assessment examines pre-earthquake livelihood conditions across the most severely affected areas—Mandalay, Sagaing, Bago, Nay Pyi Taw, and Shan State—to provide a baseline for recovery planning focused on restoring economic resilience. Prior to the earthquake, household livelihoods varied significantly across the earthquake hit regions. Farming and livestock production dominated in Shan and Sagaing, where the earthquake primarily affected rural areas, whereas non-farm businesses and salaried employment were more common in Mandalay and Nay Pyi Taw, where the earthquake impacted predominately urban areas. Wage labor, both farm and non-farm, supported a significant share of households, but was associated with the highest rates of income-based poverty, reflecting the insecurity of casual and seasonal employment. Income-based poverty was widespread, affecting 69 percent of households in earthquake-affected areas.